(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Free-living nematodes are usually the dominant component of marine and estuarine benthos, and their diversity and abundance are key to the functioning of aquatic ecosystems. The relevance and versatility of nematode community analysis in environmental biomonitoring have already been demonstrated in several oceanic and coastal studies. Nematode studies have generally been replaced by ecological studies where identification is mostly limited to the genus level. While these approaches have helped the understanding of many relevant phenomena, classical taxonomic studies, and species distribution remain crucial, especially in estuarine ecosystems, which are priority areas for biodiversity conservation and represent an important ecological and economic resource. This work aims to contribute to the taxonomic knowledge of freeliving nematodes of estuarine habitats in Uruguay, constituting the first record of 22 species. Due to the ecosystemic role of nematodes and their general lack of knowledge, it is essential to continue contributing to the taxonomic knowledge of the group in our country.